The Molecular Mechanism of Sex Hormones on Sertoli Cell Development and Proliferation - Shah, Wasim; Khan, Ranjha; Shah, Basit; Khan, Asad; Dil, Sobia; Liu, Wei; Wen, Jie; Jiang, Xiaohua (Frontiers in Endocrinology, 2021)
Sustaining and maintaining the intricate process of spermatogenesis is liable upon hormones and growth factors acting through endocrine and paracrine pathways. The Sertoli cells (SCs) are the major somatic cells present in the seminiferous tubules and are considered to be the main regulators of spermatogenesis. As each Sertoli cell supports a specific number of germ cells, thus the final number of Sertoli cells determines the sperm production capacity. Similarly, sex hormones are also major regulators of spermatogenesis and they can determine the proliferation of Sertoli cells. In the present review, we have critically and comprehensively discussed the role of sex hormones and some other factors that are involved in Sertoli cell proliferation, differentiation and maturation. Furthermore, we have also presented a model of Sertoli cell development based upon the recent advancement in the field of reproduction. Hence, our review article provides a general overview regarding the sex hormonal pathways governing the Sertoli cell proliferation and development.